METHODS OF CLINICAL-MORPHOLOGICAL EXAMINATION OF CHRONIC TONSILLITIS - Khodjanov Shokhimardon Khodjanovich; Djuraev Jamolbek Abdukaharovich; Soatov Ilyasjon Olim oglu; Shaumarov Azizkhon Zavkievich; Mardonov Khurshed Azamkul ugli (Web of Journals Publishing, 2024)
During the research, 25 patients and 25 volunteer workers were selected for the control group, who applied to the ENT polyclinic of the Tashkent Medical Academy. Pathological microflora is found in the obtained smears, the phagocytic activity of leukocytes decreases, and multinucleated types of leukocytes appear in the blood, and lymphocytes decrease.
Keywords: Chronic tonsillitis, chronic pharyngitis, lacunae, lymphocyte.